PENGARUH INVESTASI DAN UPAH MINIMUM TERHADAP PERTUMBUHAN EKONOMI DAN PENGANGGURAN KABUPATEN/KOTA DI PROVINSI BALI - Paramartha, I Dewa Gede Krisna Cipta; Suasih, Ni Nyoman Reni (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 7 (2023): Vol.12.7. JULI.2023[451-532], 2023)
The purpose of this study is to examine the effects of investment and minimum wages on economic growth and unemployment, and to examine whether economic growth can mediate the effects of investment and minimum wages on unemployment. This study uses secondary data for the period 2017-2021. The study location is in Bali and includes nine provinces and cities. The data obtained were tested using the path analysis method using Eviews 9 software. Research results show that variable investment and minimum wage can affect economic growth. The investment and minimum wage variables have no effect on the unemployment rate. Investment and minimum wage variables can affect unemployment through economic growth variables. keyword : Growth Rate, Investment Rate, Minimum Wage Rate, Economic, Unemployment Rate